Knowledge, attitudes, and practices of vaccinators about expanded programs on immunization: a cross-sectional study - Azhar, Sunia; Rashid, Laiba; Islam, Taskeen; Akhtar, Samar; Hopkins, Kathryn L.; Sommers, Theresa; Ikram, Aamer; Anwer, Naveed; Maqbool, Nabeel Ahmed; Khan, Zakir; Ahmed, Naveed; Akhtar, Hashaam (Frontiers in Public Health, 2024)
The periodic evaluation of the knowledge, attitudes, and practices (KAP) of healthcare workers including vaccinators concerning expanded programs on immunization is very crucial for a better healthcare system. This study was carried out to assess the KAP of vaccinators about the EPI including cold storage of vaccines and their practices related to vaccine cold chain management. A cross-sectional study was conducted during January to June 2022 among registered vaccinators in twin cities (Islamabad and Rawalpindi) of Pakistan. A structured self-administered questionnaire (English and Urdu version) was developed as per the Pakistan national EPI policy and strategic guidelines 2022 and World Health Organization (WHO) guidelines, and also from earlier studies (Cronbach alpha value of 0.734). The final questionnaire consisted of closed-ended questions with four sections including sociodemographic information, knowledge (dichotomous variables yes/no), attitude (a 5 point Likert scale option from strongly agree to strongly disagree) and handling of vaccines and cold chain management. Completely filled questionnaires were entered in Microsoft Excel and then imported to SPSS software version 25 for statistical analysis. A total of 186 vaccinators completely filled the questionnaire with 97.9% response rate. More than half of the participants (57.5%) had no training related to EPI. Most of the respondents had a moderate to poor level of knowledge regarding EPI. The overall attitude was positive and 57% of the participants strongly agreed that the national immunization programs can significantly contribute to the decrease the morbidity and mortality rates among children. In current study, participants showed good practices towards EPI, vaccine storage and cold chain management. Majority (93.5%) of the participants check the expiry of vaccines at regular intervals to maintain the first expiry first out (FEFO) in their healthcare setting. In conclusion, most of the vaccinators had moderate to poor knowledge, positive attitude and good practices towards EPI, vaccine cold storage, and cold chain management. Lack of training among vaccinators on EPI was also observed. These findings have suggested that continuous training, education and regular supervision of vaccinators in EPI is important for maximum immunization effectiveness and coverage.